Microstructure dependent fatigue crack growth in aged hardened aluminium alloys - Borrego, L. P. (2004)
Fatigue crack propagation tests in constant amplitude loading, as well as with single peak overloads, have been performed in AlMgSi1-T6 aluminium alloys with different Mn and Cr contents. Crack closure was monitored in all tests by the compliance technique using a pin microgauge. A moderate stress ratio and a strong material dependence effects on the fatigue crack growth were observed. These effects are discussed in terms of the different dominant closure mechanism (plasticity-induced closure or roughness-induced closure). Roughness-induced closure dominates crack closure in the alloys with higher contents of Mn and Cr elements. In the alloy with a lower content of these elements, plasticity-induced closure is dominant. When roughness-induced closure is the prime pre-overload closure mechanism, the retardation effect is decreased in comparison to when plasticity-induced closure is dominant.